ICE manual of bridge engineering - Parke, G. A. R.; Hewson, Nigel R.; Ryall, M. J. (Thomas Telford, 2008)
The fully revised, restructured and updated second edition of the ICE Manual of Bridge Engineering has been written and edited by a team of leading experts and presents valuable contributions from across the field within a single resource.